Biosensors and Molecular Imprinting - Gizem Ertürk (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Sensitive assays are often based on molecular recognition. Often stability problems have limited the use of such assays. The introduction of molecularly imprinted polymers (MIPs) eliminates such limitations. With the introduction of biosensors combined with MIPs, one gets a strong combination. This volume presents how MIPs are being produced, how MIPs are integrated in different sensor concepts and finally highlights some results in certain applications.